Differentiation between glioma and radiation necrosis using molecular magnetic resonance imaging of endogenous proteins and peptides - Zhou, Jinyuan (2010)
Distinguishing tumor recurrence from radiation necrosis following brain tumor therapy remains a major clinical challenge. Here we demonstrate the ability to distinguish these lesions using the amide proton transfer (APT) MRI signals of endogenous cellular proteins and peptides as an imaging biomarker. When comparing two orthotopic glioma models (SF188/V+ glioma and 9L gliosarcoma) with a radiation necrosis model in rats, viable glioma (hyperintense) and radiation necrosis (hypointense to isointense) could be clearly differentiated using APT MRI. When irradiating rats with U87MG gliomas, the APT signals in the irradiated tumors decreased significantly at 3 days and 6 days post-radiation. The amide protons detected by APT provide a unique and non-invasive MRI biomarker for assessing viable malignancy versus radiation necrosis and predicting tumor response to therapy.